DAILY ROUTINE OF THE TASHKENT POLICE SCHOOL DURING THE SECOND WORLD WAR (TAMADDUN NURI JURNALI, 2025)
This article describes the daily routine of the Tashkent Police School during the Second World War, personnel training, regulations adopted during those difficult times, and the activities of the police.